Massive Hemorrhage: The Role of Whole Blood Viscoelastic Assays - Scala, Emmanuelle; Marcucci, Carlo (Hämostaseologie, 2020)
Viscoelastic whole blood tests are increasingly used to guide hemostatic therapy in bleeding patients in the perioperative, trauma, and obstetric settings. Compared with standard laboratory tests of hemostasis, they have a shorter turnaround time and provide simultaneous information on various aspects of clot formation and lysis. The two available brands TEG (thromboelastography) and ROTEM (rotational thromboelastometry) provide devices that are either manually operated or fully automated. The automation allows for the assays to be used as point-of-care tests increasing their usefulness in massively bleeding patients with rapidly changing hemostatic profiles. While the number of research papers on the subject and the number of published treatment algorithms increase rapidly, the influence of the use of these devices on patient outcome needs yet to be established. In this article, we first review the technology of these devices and the parameters provided by the assays. Next, we present the problems encountered when choosing cut-off values that trigger intervention. Furthermore, we discuss the studies examining their influence on clinical outcomes, and finally, we briefly highlight some of the most important limitations and pitfalls inherent to these assays.
Keywords: bleeding; transfusion; viscoelastic tests